(untitled) (Research, Society and Development, 2020)
The Wheel of Life is a self-assessment system, composed of 12 spheres, where the center of the wheel is the point zero of satisfaction and the other end the maximum value, positive, desirable and possible with the goal and self-knowledge distributed in the triads of relationship, person, quality of life and professional. The objective was to analyze through the Wheel of Life the students’ perception of the work safety and chemistry course of the Federal Institute of Rio de Janeiro, São Gonçalo campus, the levels of current satisfaction in the various areas of life. This study was developed by means of a qualitative, quantitative and deductive approach, with exploratory and descriptive procedures, the data collection was performed by applying the Wheel of Life from a guiding question "How did I get here?". 136 students of both sexes were part of the survey. It was identified that of the 9 spheres, 7 were within the desirable mean of satisfaction, while the other 2 spheres were below the desirable mean. It is important to evaluate the dimensions of students’ lives in stages, in order to identify changes in quality of life. The Wheel of Life was favorable to self-reflection and sharing of their experiences.